Bola Bali Maning Games Movement Activity to Physical Fitness Improvement - Nurharsono, Tri; Rahayu, Tandiyo; Sulaiman, Sulaiman; Hartono, Mugiyo (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Elementary school children experience development in all aspects, both in terms of physical, psychological and sociological. In the field of motor skills, elementary school-age children have entered basic movement patterns and becoming skilled requires practice. They also need training for social maturity and physical fitness improvement. Games combined with the Teaching Personal and Social Responsibility (TPSR) approach can develop physical abilities, movement coordination, psychology, and social skills according to the characteristics of elementary school students. The purpose of this study was to produce a product model for learning physical fitness material for elementary school students in grades II with the TPSR approach. The research design used is Research and Development. This research was conducted in elementary schools in the Semarang City, Central Java, Indonesia. The entire population was used as a research sample of 209 students. Data collection techniques using observation. The experimental data were analyzed descriptively analytically. The results showed that the physical education development model of fitness material with the TPSR approach was carried out through the Bola Bali Maning (Back Ball Match/ BBM) games. The results of small-scale and large-scale tests for assessing attitudes, knowledge and skills in physical fitness material show that the TPSR approach has an effect on student character with a p-value for each assessment of 0.000 0.05. It can be concluded that the development of a physical education learning model for fitness with the TPSR approach through BBM games is effective in improving students' knowledge, attitudes and skills.